Efficient Hybrid-Spectral Model for Fully Nonlinear Numerical Wave Tank - Christiansen, Torben B.; Bingham, Harry B.; Engsig-Karup, Allan P.; Ducrozet, Guillaume; Ferrant, Pierre (Volume 9: Odd M. Faltinsen Honoring Symposium on Marine Hydrodynamics, 2013)
International audience A new hybrid-spectral solution strategy is proposed for the simulation of the fully nonlinear free surface equations based on potential flow theory. A Fourier collocation method is adopted horisontally for the discretization of the free surface equations. This is combined with a modal Chebyshev Tau method in the vertical for the discretization of the Laplace equation in the fluid domain, which yields a sparse and spectrally accurate Dirichlet-to-Neumann operator. The Laplace problem is solved with an efficient Defect Correction method preconditioned with a spectral discretization of the linearised wave problem, ensuring fast convergence and optimal scaling with the problem size. Preliminary results for very nonlinear waves show expected convergence rates and a clear advantage of using spectral schemes.